2023
DOI: 10.46303/jcsr.2023.25
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Computer Aided Education in the Education of Folk Cultural Products

Zhanat Aimukhambet,
Saulesh Aituganova,
Aslan Alimbayev
et al.

Abstract: This research explores the effects of computer-aided education (CAE) on the education of folk cultural products. Folklore, encompassing tangible and intangible cultural artifacts, holds significant importance in defining the identity and values of a community. CAE, utilizing multimedia software and interactive teaching methods, has emerged as a promising approach to enhancing student learning experiences. This study aims to investigate the impact of CAE on students' achievement, retention, cultural competency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…When language teaching is reduced to simply vocabulary instruction, it is ineffective. Today's language teaching approaches favor using materials representing environmental variables, geographical location, and culture (Aimukhambet et al, 2023;Turayevich, 2021).…”
Section: Toponomy In Kazakh and Nogai Languagesmentioning
confidence: 99%
“…When language teaching is reduced to simply vocabulary instruction, it is ineffective. Today's language teaching approaches favor using materials representing environmental variables, geographical location, and culture (Aimukhambet et al, 2023;Turayevich, 2021).…”
Section: Toponomy In Kazakh and Nogai Languagesmentioning
confidence: 99%
“…These research studies show inconsistency in their findings. Some concluded that computer assisted instruction could improve students' academic performance (Belias, Sdrolias, Kakkos, Koutiva & Koustelios, 2013;De Witte, Haelermans & Rogge, 2015;Wenceslao, 2022;Aimukhambet et al, 2023) while some studies revealed no significant difference in students' academic performance (Tsami, 2010). That is why there are still researches on issues and debates on the desirability of technology in imparting learning (Selwyn, 2017), and on the extent of use of computer to impart learning on students in the classroom teaching (Cuban, 2001).…”
Section: Review Of Related Literaturementioning
confidence: 99%